Penerapan Model Detective Case-Solving Game dalam Pengajaran Narrative Language Features di SMKN 3 Palangka Raya - Rahma Ibtida Saumi; Sabarun Sabarun (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to enhance students’ understanding of narrative language features at SMKN 3 Palangka Raya through the implementation of the Detective Case-Solving Game model. The method applied was participatory learning, involving 36 eleventh-grade Computer and Network Engineering students in two sessions. The first meeting focused on introducing the game concept, including rules, character roles, and examples of narrative clues, while the second meeting emphasized the application of more complex case scenarios that required deeper analysis and storytelling skills. The results revealed a significant improvement in students’ ability to identify narrative structures, apply past tense, and use direct–indirect speech correctly. Moreover, students showed higher enthusiasm, actively engaged in group discussions, demonstrated teamwork, and were able to provide linguistic reasoning during presentations. In conclusion, this model effectively strengthens language skills while fostering 21st-century competencies, including critical thinking, communication, collaboration, and creativity, making the learning process more interactive, enjoyable, and meaningful for vocational students.